Assessing the performance of five adult mosquito sampling methods for malaria vector surveillance in various ecosystems in Cameroon - Nwane, Philippe; Piameu, Michael; Emalio, Yannick Niamsi; Ekoko, Wolfgang Eyisap; Mandeng, Stanislas Elysée; Mbakop, Lili Ranaise; Patchoke, Salomon; Toto, Jean-Claude; Alenou, Leo Dilane; Bikoi, Elisabeth Ngo; Onguina, Hugues; Nvondo, Narcisse; et al. (Frontiers in Tropical Diseases, 2024)
Introduction Many sampling methods are used for entomological surveillance of vector borne diseases. This paper, evaluated the performance of five methods with regard to various ecosystems encountered in Cameroon. Material and methods Two entomological databases generated during two study periods were examined: 2011-2014 in the North Region, and 2018-2019 in the Centre Region. Mosquitoes were collected using the (Human Landing Catches) (HLC) and four alternative methods including Clay Pots (CPs), Pyrethroid Spray Catches (PSCs), Window Exit Traps (WETs) and Centers for Disease Control-Light Traps (CDC-LTs) for which the performance was assessed in this study. Results A total of 29 anopheline species were identified from samples collected during the two study periods. All these anopheline species were found in North Region, with 5 species being the most abundant and prévalent, i.e. An. gambiae s.l, An. funestus, An. rufipes, An. paludis and An. pharoensis. In the Centre Region, only five species including An. gambiae s.l, An. funestus, An. coustani, An. ziemanni and An. paludis were recorded. Among these, An. gambiae s.l was the most abundant and prevalent species. Data confirmed HLC as the best in sampling outdoor and indoor mosquitoes in the surveyed HDs. The alternative methods showed variable records regarding the species richness. Based on the number of mosquitoes collected, CP was an alternative to HLC for outdoor collections in Garoua and Pitoa HDs, while WET was an alternative in Mayo Oulo HD. In the Centre Region, CDC-LT was an alternative to HLC for indoor collections in Ekié and Nkolbisson HDs, while PSC proved to be the best alternative in Nkolondom HD. Regarding the species richness WET appeared as an alternative to HLC in sampling outdoor mosquitoes in Garoua and Mayo Oulo HDs, while CP was the best alternative in Pitoa HD. In the Centre Region, CDC-LT was an alternative for outdoor and indoor collections in Nkolbisson HD, and the best alternative for outdoor collections in Ekie HD. Conclusion The current study revealed variable performance of the five tested adult mosquito collection methods across the prospected HDs in North and Centre Regions of Cameroon. Further investigations will be conducted on other collection methods, e.g., aspiration, mosquito electrocuting grid trap, ovitraps and human-baited double net trap.